2022
DOI: 10.1016/j.sjbs.2021.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kolaviron on islet dynamics in diabetic rats

Abstract: Kolaviron, a biflavonoid isolated from the edible seeds of Garcinia kola , lowers blood glucose in experimental models of diabetes; however, the underlying mechanisms are not yet fully elucidated. The objective of the current study was to assess the effects of kolaviron on islet dynamics in streptozotocin-induced diabetic rats. Using double immunolabeling of glucagon and insulin, we identified insulin-producing β- and glucagon-producing α-cells in the islets of diabetic and control rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Though there is no generally accepted mechanism of action yet, KV was suggested to produce its antidiabetic effect via inhibition of α-glucosidase and α-amylase activities (Iwu et al 1990b ; Salau et al 2020 ). Recent study has also suggested that KV may play a regenerative role in pancreatic islets in streptozotocin-induced diabetic rats (Oyenihi et al 2021 ). Other studies focused on the KV ability to reduce secondary pathology complications associated with diabetes, including hepatoxicity, nephrotoxicity, and cardiotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Though there is no generally accepted mechanism of action yet, KV was suggested to produce its antidiabetic effect via inhibition of α-glucosidase and α-amylase activities (Iwu et al 1990b ; Salau et al 2020 ). Recent study has also suggested that KV may play a regenerative role in pancreatic islets in streptozotocin-induced diabetic rats (Oyenihi et al 2021 ). Other studies focused on the KV ability to reduce secondary pathology complications associated with diabetes, including hepatoxicity, nephrotoxicity, and cardiotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacological properties of GK seeds are attributed to their complex mixture of biflavonoids, polyphenolic compounds, and prenylated benzophenones. Kolaviron is one of the biflavonoids that are extracted from GK seeds and is known as the most active phytochemical in these seeds [ 208 ]. Normal consumption levels of GK seeds are considered safe for human [ 207 ].…”
Section: Natural Products and Compounds As Possible Agents To Counter...mentioning
confidence: 99%